An Infrared Ultra-Broadband Absorber Based on MIM Structure - Meichen Li; Guan Wang; Yang Gao; Yachen Gao (Nanomaterials, 2022)
We designed an infrared ultra-broadband metal–insulator–metal (MIM)-based absorber which is composed of a top layer with four different chromium (Cr) nano-rings, an intermediate media of aluminum trioxide (Al2O3), and a bottom layer of tungsten (W). By using the finite-difference time-domain (FDTD), the absorption performance of the absorber was studied theoretically. The results indicate that the average absorption of the absorber can reach 94.84% in the wavelength range of 800–3000 nm. The analysis of the electric and magnetic field indicates that the ultra-broadband absorption rate results from the effect of local surface plasmon resonance (LSPR). After that, the effect of structural parameters, metal and dielectric materials on the absorptivity of the absorber was also discussed. Finally, the effect of incidence angle on absorption was investigated. It was found that it is not sensitive to incidence angle; even when incidence angle is 30°, average absorptivity can reach 90%. The absorber is easy to manufacture and simple in structure, and can be applied in infrared detection and optical imaging.